Solar UV Index at Different Altitudes of Nepal - Sharma, Niranjan Prasad (Journal of the Institute of Engineering, 2018)
The main objective of this research is to study the satellite estimated solar Ultraviolet data alongside the ground based data in Nepal. Kathmandu (27.72°N, 85.32°>E), Pokhara (28.22°N, 83.32°E) Biratnagar (26.45°N, 87.27°E) and Lukla (27.69°N, 86.73°E) are located at an elevation of 1350m, 800m, 72m and 2850m respectively from the sea level. The ground based measurements and the satellite estimation were performed by NILU-UV irradiance meter and EOS Aura OMI satellite respectively. The NILU-UV irradiance meter is a six channel radiometer designed to measure hemispherical irradiances on a flat surface. Meanwhile the Ozone Monitoring Instrument (OMI) on board, the NASA EOS Aura space craft is a nadir viewing spectrometer that measures solar reflected and back scattered light in ultraviolet and visible spectrum. The study was performed for 3 years Ultraviolet Radiation (UVR) data. This study showed that the ratio of predicted OMI Ultraviolet Index (UVI) to that determined from the ground based measurement was less than 1.21 except in Lukla. Journal of the Institute of Engineering, 2018, 14(1): 200-205